Separation after childbirth and the psychological, social and physical implications: ethnographic insights from a neonatal intensive care unit - Bjerregaard, Michella; Axelin, Anna; Poulsen, Ingrid; Brødsgaard, Anne (BMJ, 2026)
Objective: To investigate the context of separations among mother, father and infant after childbirth, with a focus on the psychological, social and physical implications of these separations.
Design: A short-term ethnographic study, which included participant observations and informal interviews. Data were analysed by a partly deductive content analysis inspired by Graneheim and Lundman.
Setting: A '27-bed' Danish neonatal intensive care unit.
Participants: The study included parents (n=19) who had an infant in need of intensive care and were separated after childbirth.
Findings: The study identified an overarching theme of navigating family dynamics, caregiving and emotional challenges during separation. Three interconnected subthemes-Physical and virtual bonding as a necessity, Nurturing and caregiving shifts and Collective emotional impact of separation-shed light on the disjointed and emotional nature of parent-infant separation in neonatal care.
Conclusions: The findings revealed that the first hours in the neonatal intensive care unit were often characterised by disjointed rather than unified care, as nurses balanced their focus across the family while parents navigated the emotional strain of separation. Organisational and structural barriers further challenged reunification, highlighting the need for care models prioritising proximity, family bonding and minimised separation.
Keywords: Family; Neonatal intensive & critical care; Nursing Care; QUALITATIVE RESEARCH.
© Author(s) (or their employer(s)) 2025. Re-use permitted under CC BY-NC. No commercial re-use. See rights and permissions. Published by BMJ Group.